Persistent Penumbra in a Rabbit Stroke Model: Incidence and Histologic Characteristics - Leah J. Hennings; Rene Flores; Paula K. Roberson; Aliza Brown; John Lowery; Michael Borrelli; William C. Culp (Stroke Research and Treatment)
Duration and extent of penumbra determine the window and brain volume in which interventions may save injured tissue after stroke. Understanding the penumbra in animals is necessary in order to design models that translate to effective clinical therapies. New Zealand white rabbits were embolized with aged autologous clot (n=23) or insoluble microspheres (n=21). To examine effects of treatment on penumbra, sphere-stroked animals were treated with 3 μm microbubbles plus ultrasound (n=19). Rabbits were euthanized at 4 or 24 hr. Infarct volume was measured following triphenyltetrazolium chloride (TTC) staining of brain sections. Penumbra was visualized using immunostaining of pimonidazole injected fifteen minutes prior to euthanasia. Potentially reversible penumbra was present in 14.3% stroked rabbits at 4 hours and 15.7% at 24 hours after embolic stroke and represented up to 35% of total lost tissue. Intervention at up to 24 hours may benefit a significant patient population.